2022
DOI: 10.1186/s12967-022-03351-5
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of acute kidney injury after cardiac surgery: model development using a Chinese electronic health record dataset

Abstract: Background Acute kidney injury (AKI) is a major complication following cardiac surgery that substantially increases morbidity and mortality. Current diagnostic guidelines based on elevated serum creatinine and/or the presence of oliguria potentially delay its diagnosis. We presented a series of models for predicting AKI after cardiac surgery based on electronic health record data. Methods We enrolled 1457 adult patients who underwent cardiac surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Given that the occurrence of AKI is a dynamic process and is particularly affected by procedurerelated factors, we suggest that all preoperative, intraoperative, and early postoperative parameters should be screened for assessment during model derivation. 26 Taken together, these data indicated that the study end point, race, and sample source are still pivotal factors and different models may be more suitable to apply to local populations.…”
Section: Discussionmentioning
confidence: 95%
“…Given that the occurrence of AKI is a dynamic process and is particularly affected by procedurerelated factors, we suggest that all preoperative, intraoperative, and early postoperative parameters should be screened for assessment during model derivation. 26 Taken together, these data indicated that the study end point, race, and sample source are still pivotal factors and different models may be more suitable to apply to local populations.…”
Section: Discussionmentioning
confidence: 95%
“…Creatinine is a typical indicator of kidney injury in the clinic that has been linked to various other diseases ( 28 ). Acute kidney injury is one of the most common and serious complications of cardiac surgery, and it can substantially impact the morbidity and mortality of patients ( 29 , 30 ). Cardiac surgery-associated acute kidney injury has a complicated pathogenesis, mainly involving inflammatory response, ischemia-reperfusion injury, metabolic disorder, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk scores based on these factors have been developed (Table 3 ). After the introduction of traditional clinical scores [ 40 43 ], new scores have applied various methods to improve predictive performance, such as adding biomarkers [ 44 , 45 ], laboratory test-based [ 46 , 47 ], and using machine learning technology [ 48 ] to build predictive models. These scores have been reported with diagnostic accuracy in the range of 70–85%.…”
Section: Definition and Diagnosismentioning
confidence: 99%